Challenging the current climate change – migration nexus: exploring migrants’ perceptions of climate change in the hosting country - de Guttry, Corinna; Döring, Martin; Ratter, Beate (DIE ERDE: Journal of the Geographical Society of Berlin, 2016)
Along with the growing scientific and political concern on global warming, the relationship of climate and migration is framed as cause and consequence. Alarmist numbers of mass migration and related conflicts currently represent the main scientific narratives merging the issue of migration and climate change. This paper takes a different and explorative perspective: it suggests that scientific discourses on migration and climate change should be reframed by taking into consideration the diverse ‘knowledges’ offered by migrants. Employing an experimentalist approach, we aim at filling this gap in research and introduce an empirical perspective on climate framings among Italian and Chinese citizens in the local context of the city of Hamburg (Germany). Qualitatively analysing semi-structured interviews, the paper conveys an in-depth analysis of how Italian and Chinese migrants frame climate change and, furthermore, explores philosophical backgrounds informing them. We start with a theoretical and methodological outline on undertaking research with migrants and then turn to an empirical analysis in which we examine and discuss four prevailing categories found in the course of our investigation. The final section summarises the results and reflects upon the methodological and theoretical approach applied which refers to the relevance of migrants as active actors in local adaptation and mitigation processes of the hosting country.